Sistem Rancang Bangun dalam Islam - Mu’awwanah, Uliyatul; Ridho Illah, Ghoni Rizky; Lestari, Dian (Al-tsaman : Jurnal Ekonomi dan Keuangan Islam, 2023)
Islamic economics is an economy that is built on the basis of values ​​taken from Islamic law. the values ​​contained form an Islamic economic design which will later provide an overview for realizing the goals of Islamic economics. In the design of Islamic economics there are important components including Islamic economic theory, principles of Islamic economic systems, and Islamic behavior in business and economics. These three important components become important research as a means to be applied and related to economic behavior both in daily life and applied in the state. The purpose of this research is to convey knowledge from the title which is made so that it can be useful and applied by every individual in carrying out good economic activities and can create a just and prosperous economy. The method used in this research is to use a qualitative method by taking and collecting sources from literature studies. The result of this discussion is that Islamic economic design is a very important feature in building a just and prosperous economic system in accordance with the goals of Islamic economics